Measuring digital stress in Norway: translation and validation of the Digital Stressors Scale - Sevic, Aleksandra; Foldnes, Njål; Brønnick, Kolbjørn Kallesten (Frontiers in Psychology, 2024)
Introduction A better understanding of the effects of the widespread use of information and communication technology (ICT) among employees is important for maintaining their wellbeing, work-life balance, health, and productivity. Thus, having robust and reliable measurement instruments is crucial for quantifying the effects of ICT use, and facilitating the development of effective strategies to promote employee wellbeing. Methods Therefore, we translated the Digital Stressors Scale (DSS) to Norwegian and administered it to a convenience sample of 1,228 employees, using the forward-backward translation method. The DSS is a new multidimensional scale consisting of 50 items that measure 10 digital stressors (first-order factors), and a second-order factor of DSS. We assessed the scale's construct validity with confirmatory factor analysis, first by assessing the model fit of each of the sub-scales separately, to facilitate the disaggregated measurement approach, and then the model fit of the whole scale with the second-order factor. Results Among the participants, 45.6% completed the whole questionnaire (n = 560). The original solution's fit was unsatisfactory in our sample, which led us to perform an exploratory factor analysis. We propose a shorter 8-factor scale with 37 of the original items, which also shows good internal consistency for all the first-order factors. Discussion We argue that the disaggregated approach is beneficial for the investigation of the specific creators of digital stress and that conceptually sound measurement models are needed in order to facilitate a more rigorous empirical investigation of digital stressors.